Factors Influencing the Success Rates of In Vitro Fertilization (IVF) in Indonesian Couples: A Multicenter Study - Sony Sanjaya; Wisnu Wardhana Putra; Theresia Putri Sinaga; Tanvir Ahmed (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: In vitro fertilization (IVF) has become an increasingly important assisted reproductive technology for infertile couples in Indonesia. However, success rates remain variable. This multicenter study aimed to identify the factors influencing IVF success rates in Indonesian couples. Methods: A retrospective cohort study was conducted involving 1,245 couples who underwent IVF at three fertility centers in Indonesia between January 2019 and December 2022. Data were collected on demographic characteristics, infertility diagnoses, IVF protocols, and treatment outcomes. The primary outcome was live birth rate per embryo transfer. Multivariable logistic regression analysis was performed to identify independent predictors of IVF success. Results: The overall live birth rate per embryo transfer was 32.7%. Female age was a significant predictor of live birth, with success rates declining steadily after age 35. Other factors associated with higher success rates included the use of intracytoplasmic sperm injection (ICSI), blastocyst transfer, and a higher number of oocytes retrieved. Male factor infertility, endometriosis, and a history of previous failed IVF attempts were associated with lower success rates. Conclusion: This study identified several key factors influencing IVF success rates in Indonesian couples. Female age, ICSI utilization, blastocyst transfer, and oocyte yield were significant predictors of live birth. These findings can help clinicians counsel patients and optimize treatment strategies to improve IVF outcomes.